2011
DOI: 10.1139/w11-042
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical studies on the production of neuraminidase by environmental isolates ofVibrio choleraenon-O1 from Bulgaria

Abstract: Neuraminidase is a key factor in the infectious process of many viruses and pathogenic bacteria. The neuraminidase enzyme secreted by the etiological agent of cholera - Vibrio cholerae О1 - is well studied in contrast with the one produced by non-O1/non-O139 V. cholerae. Environmental non-O1/non-O139 V. cholerae isolates from Bulgaria were screened for production of neuraminidase. The presence of the neuraminidase gene nanH was detected in 18.5% of the strains. Тhe strain showing highest activity (30 U/mL), V.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Two of the reference strains used in the antibacterial activity assay, Escherichia coli NBIMCC 3397 and Pseudomonas aeruginosa NBIMCC 1390, were purchased from the National Bank for Industrial Microorganisms and Cell Cultures, Bulgaria. Klebsiella pneumoniae G31 (NBIMCC 8650) and Vibrio cholerae non-O1 strain V13 (NBIMCC 8715) were isolated and identified previously and deposited in the same culture collection [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Two of the reference strains used in the antibacterial activity assay, Escherichia coli NBIMCC 3397 and Pseudomonas aeruginosa NBIMCC 1390, were purchased from the National Bank for Industrial Microorganisms and Cell Cultures, Bulgaria. Klebsiella pneumoniae G31 (NBIMCC 8650) and Vibrio cholerae non-O1 strain V13 (NBIMCC 8715) were isolated and identified previously and deposited in the same culture collection [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was described previously that bacterial sialidases optimal temperature was in the range of 35 to 40°C (22). In Vibrio cholerae non-O1 and Arcanobacterium pyrogenes the neuraminidase enzyme was found to be thermo-tolerant and was found to be stable up to 55 to 60°C (23,24). The optimal pH in V. cholerae non-O1 was 5.4, however, the SA was found to be stable at pH 8.2 (24).…”
Section: Characterization Of Sialidase Enzyme In L Monocytogenesmentioning
confidence: 97%
“…In Vibrio cholerae non-O1 and Arcanobacterium pyrogenes the neuraminidase enzyme was found to be thermo-tolerant and was found to be stable up to 55 to 60°C (23,24). The optimal pH in V. cholerae non-O1 was 5.4, however, the SA was found to be stable at pH 8.2 (24). The sialidase enzyme was found to be quite diverse and different molecular mass was observed.…”
Section: Characterization Of Sialidase Enzyme In L Monocytogenesmentioning
confidence: 98%
“…However, high occurrences of the nanH gene were present in intestinal samples of the aquatic products collected in the Guangming Aquatic Product Base in Shanghai in November 2020. Microaerophilic environments in the intestinal epithelium and sediment lake mud may benefit the survival of V. cholerae (9). Occurrences of V. cholerae isolates of clinical and environmental origins carrying the target genes have been reported (4,13).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the zot gene encodes a zonula occludens toxin that increases transcellular ion transport and contributes to diarrhea in cholera, whereas the ace gene encodes an accessory cholera enterotoxin that disturbs small-intestinal tight junction permeability (11,18,20). In addition, previous studies have indicated that a cri gene is an important virulence-related gene required for toxin-linked cryptic plasmid replication in V. cholerae (26), whereas a nanH gene encodes a neuraminidase that is a key factor in the infectious process of many viruses and pathogenic bacteria (9). Thus, monitoring of these virulence-related genes of V. cholerae is imperative for assuring food safety and human health.…”
mentioning
confidence: 99%